Effects of Organic Manure on Growth and Yield of Lettuce (Lactuca sativa) - Jelagat, Edna (University of Embu, 2019)
This research was carried out at the university of Embu farm to determine the yield of lettuce (Lactuca sativa) when fertilized with cow manure. The treatments were cow manure applied at the rates of 0 t/ha, 5 t/ha, 15 t/ha and 20 t/ha. The results showed that growing lettuce using the four treatments significantly influenced their growth rate, leaf number, height of the plant, fresh weight and dry weight. Lettuces grown with cow manure at the rate of 20 t/ha were found to have higher leaf number, fresh weight and dry weight. Lettuce gown using cow manure at the rate of 0 t/ha had the least leaf number, fresh weight and dry weight. Among the manure treatments, cow manure at the rate of 5 t/ha had the least leaf number, fresh weight and dry weight followed by lettuce grown with cow manure at the rate of 15t/ha. The application of cow manures at the rate of 20 t/ha is preferred as it was associated with higher leaf number, fresh weight and dry weight of lettuce. The application of cow manure at the rate of 20 t/ha is therefore recommended for farmers to use to obtain higher yields of lettuce.